Análisis económico financiero de la Cooperativa de Ahorro y Crédito Las Naves Ltda del cantón Las Naves, provincia Bolívar, Año 2017 - Vega García, Dina Isabel (2018)
The financial economic analysis is a work method or tool, through which a comparative analysis can be made with the financial indicators that are carried out by the Savings and Credit Cooperatives that are supervised by the Superintendency of Popular and Solidarity Economy. It was very important to develop a financial economic analysis in the Cooperative of Savings and credit Las Naves, as there are many shortcomings at the time of decisionmaking. In order to develop this present research work we used the data collection instruments such as, the counters to the accountant, the manager, the surveillance council and the administrative council, which are the ones involved at the time of decision making. Through the collection of data and information, the interpretation and analysis of results could be carried out to continue the PERLAS economic analysis proposal, which will allow an in-depth analysis of the financial statements to improve and identify the economic situation of the institution.